Metagenomic next-generation sequencing for identification of central nervous system pathogens in HIV-infected patients - Zhu, Yunqi; Zhao, Wenxuan; Yang, Xihong; Zhang, Yuanyuan; Lin, Xiaoling; Weng, Xing; Wang, Yali; Cheng, Cong; Chi, Yun; Wei, Hongxia; Peng, Zhihang; Hu, Zhiliang (Frontiers in Microbiology, 2022)
Although considerable interest in metagenomic next-generation sequencing (mNGS) has been attracted in recent years, limited data are available regarding the performance of mNGS in HIV-associated central nervous system (CNS) infection. Here, we conducted a retrospectively analyzing of the cerebrospinal fluid (CSF) mNGS reports and other clinical data from 80 HIV-infected patients admitted to the Second Hospital of Nanjing, China from March, 2018 to March, 2022. In our study, CSF mNGS reported negative result, mono-infection, and mixed infection in 8.8%, 36.2% and 55% of the patients, respectively. Epstein-Barr virus (EBV), positive in 52.5% of samples, was the most commonly reported pathogen, followed by cytomegalovirus (CMV), John Cunningham virus (JCV), torque teno virus (TTV), cryptococcus neoformans (CN), toxoplasma Gondii (TE), and mycobacterium tuberculosis (MTB). 76.2% of the EBV identification and 54.2% of the CMV identification were not considered clinically important, and relative less sequence reads were reported in the clinical unimportant identifications. The clinical importance of the presence of TTV in CSF was not clear. Detection of JCV, CN or TE was 100% suggestive of specific CNS infection, however, 60% of the MTB reports was considered contamination. Moreover, of the 44 (55%) mixed infections reported by mNGS, only 4 (5%) were considered clinical important, and mNGS failed to identify 1 mixed infection. Additionally, except for MTB, CSF mNGS tended to have high sensitivity to identify the above-mentioned pathogens (almost with 100% sensitivity). Even all the diagnostic strategies were evaluated, the cause of neurological symptoms remained undetermined in 6 (7.5%) patients. Overall, our results suggest that mNGS is a very sensitive tool for detecting common opportunistic CNS pathogen in HIV-infected patients, although its performance in CNS tuberculosis is unsatisfactory. EBV and CMV are commonly detected by CSF mNGS, however, the threshold of a clinical important detection remains to be defined.